Ultralight and Flexible Monolithic Polymer Aerogel with Extraordinary Thermal Insulation by A Facile Ambient Process. Issue 13 (27th May 2019) - Li, Man; Qin, Zihao; Cui, Ying; Yang, Chiyu; Deng, Changyu; Wang, Yunbo; Kang, Joon Sang; Xia, Hongyan; Hu, Yongjie
Abstract: High performance thermal insulation materials are desired for a wide range of applications in space, buildings, energy, and environments. Here, a facile ambient processing approach is reported to synthesize a highly insulating and flexible monolithic poly(vinyl chloride) aerogel. The thermal conductivity is measured respectively as 28 mW (m K) −1 at atmosphere approaching the air conductivity and 7.7 mW (m K) −1 under mild evacuation condition. Thermal modeling is performed to understand the thermal conductivity contributions from different heat transport pathways in air and solid. The analysis based on the Knudsen effect and scattering mean free paths shows that the thermal insulation performance can be further improved through the optimization of porous structures to confine the movement of air molecules. Additionally, the prepared aerogels show superhydrophobicity due to the highly porous structures, which enables new opportunities for surface engineering. Together, the study demonstrates an energy‐saving and scalable ambient‐processing pathway to achieve ultralight, flexible, and superhydrophobic poly(vinyl chloride) aerogel for thermal insulation applications. Abstract : Ultralight and flexible monolithic polymer aerogel with extraordinary thermal insulation and superhydrophobic properties are developed using a facile ambient processing method.